The neutrophil-to-lymphocyte ratio as a prognostic biomarker in Guillain-Barre syndrome: a systematic review with meta-analysis - Cabanillas-Lazo, Miguel; Quispe-Vicuña, Carlos; Cruzalegui-Bazán, Claudia; Pascual-Guevara, Milagros; Mori-Quispe, Nicanor; Alva-Diaz, Carlos (Frontiers in Neurology, 2023)
Background and objectives: Guillain‒Barré syndrome (GBS) is an immune-mediated neuropathy. This characteristic indicates that the neutrophil-lymphocyte ratio (NLR) may be a biomarker of its activity. We conducted a systematic review and meta-analysis to summarize the evidence on the NLR as a potential biomarker for GBS. Methods: We systematically searched databases (PubMed, Ovid-Medline, Embase, Scopus, Web of Science, Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), and Google Scholar) until October 2021 for studies evaluating pretreatment NLR values in GBS patients. A meta-analysis using a random-effects model to estimate pooled effects was performed for each outcome, and narrative synthesis was used when this was not possible. Subgroup and sensitivity analyses were performed. Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) criteria were used to assess the certainty of evidence for each result. Results: Ten studies from 745 originally included were selected. In comparisons between GBS patients and healthy controls, a meta-analysis of six studies (968 patients) demonstrated significantly higher NLR values in GBS patients (mean difference (MD): 1.76; 95% CI: 1.29, 2.24; I2 = 86%) with moderate certainty due to heterogeneity and irrespective of the GBS diagnostic criteria used. Regarding GBS prognosis, which was considered unfavorable when Hughes Scores were ≥3, analysis based on the NLR had a sensitivity ranging from 67.3 to 81.5 and a specificity from 67.3 to 87.5 with low certainty due to imprecision and heterogeneity. Regarding assessments of respiratory failure, NLR analysis had a sensitivity of 86.5 and specificity of 68.2 with high and moderate certainty, respectively. Discussion: With moderate certainty, the mean NLR is higher in GBS patients than in healthy controls. Furthermore, we found that the NLR could be a prognostic factor for disability and respiratory failure with low and moderate certainty, respectively. These results may prove useful for applying the NLR to evaluate GBS; however, further research is needed.